ANALISA PERBANDINGAN HASIL PENGUKURAN KOORDINAT DAN ELEVASI DENGAN ALAT TOTAL STATION DAN GPS GEODETIC DI FOLDER SANGATTA KAB. KUTAI TIMUR - SUHENI, DENNY (KURVA S JURNAL MAHASISWA, 2014)
Measurement of the position of the dots by using a method ektraterestrial GPS receiversare now widely used. This is supported by advances in technology so that the results have a highaccuracy with a relatively short time. This study aims to assess the extent to which comparisonscoordinates and elevation measurements obtained from the measurement results using TotalStation Spectrafocus 8 "and SP80 Geodetic GPS.From the results of measurement and data processing in which the result of the differencein the coordinates of Total Station spectra focus 8 "with geodetic GPS sp80 spectra of 0.009meters, while the result of the difference in elevation of Total Station spectra focus 8" withgeodetic GPS sp80 at 0,011 meter